A study on the utilization of free or open source software in selected University of the Philippines Diliman Libraries - Reyes, Gaecelle E.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study aimed to determine the advantages and disadvantages of using Free or Open Source Software applications in the library. Free or Open Source Software (FOSS) in this study referred to software that is either free to download, as in zero-cost, or free to access the source code, or both. It also sought to know the following: 1) Free or Open Source Software (FOSS) applications currently used by library staff in UP libraries; 2) reasons why the library decided to use them; 3) the length of time these applications have been utilized; 4) risks and problems involved in using FOSS; 5) solutions adopted; and finally, 6) library services or functions where they are using FOSS applications.
Survey questionnaires were distributed to the Engineering I and II library staff and to the section heads of the Main Library and were collected within two weeks. Out of the sample size of 20 respondents, only 16 forms were returned. Two respondents from this population were considered system administrators. They were given a different set of questionnaires.
The results showed that features, security and support have been checked as reasons of acquisition and usage of FOSS applications, but cost scored the highest. Other reasons include" software licensing issue" and "political and personal advocacy". Based on the tally sheet, all respondents (100) were using Mozilla Firefox and iLib. They were also used very often, more than twice a week to everyday. Operating Systems such as Ubuntu and Opensuse, and other applications such as Adobe, Acrobat Reader, OpenOffice and its components, WinAMP, RAR and ZIP, Avira, Anti Vir and AVG were among those with the highest percentage of users based on the total number of responses. For the system administrators, Apache, MySQL, Joomla, Drupal, Wordpress, OpenOffice Base, GIMP, and Google Picase all had 100 response rate.
The library services and functions where FOSS applications are being utilized include circulation, cataloging, indexing, inventory, digitization, collection development, reference service, administrative works and student's database. Problems encountered in the utilization were compatibility issues, adjustment period for the staff to learn the system, and discontinuity of programs "either due to obsolescence or change of technology" without prior notice.
Solution that has been applied was to use both FOSS and proprietary applications since some library services require programs they say FOSS don't have yet. Nonetheless, FOSS advantages still won over its disadvantages in this study. FOSS applications were evaluated in general based on interoperability, user interface, functionality, documentation, maintenance, cost, and support. It had an overall rating of Good by using mode to generate the outcome. Primary recommendation is to conduct trainings, seminars of conferences on Free or Open Source Software to facilitate learning and awareness to its users
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman Libraries; Open source software